Global burden and risk factors of childhood cardiovascular disease (1990–2021) - Hou, Caixia; Zhang, Nan; Liu, Chao; Gao, Weijun (Frontiers in Public Health, 2025)
BackgroundChildhood cardiovascular disease (CCVD) is a significant global health threat, with early risk factor accumulation potentially exerting profound impacts on cardiovascular health in adulthood. However, global data analyses on the burden of CCVD remain limited, particularly regarding variations across socio-demographic index (SDI) levels and effects of major risk factors.ObjectiveThis study aimed to investigate worldwide patterns in the incidence and mortality of CCVD between 1990 and 2021 and examine how these trends vary by SDI, gender, age, and major environmental risk factors.MethodsThis study analyzed the incidence, mortality, and estimated annual percentage change (EAPC) of CCVD in children aged 0 to 14 years during 1990–2021. Descriptive statistics, group comparisons, and correlation analyses were employed to evaluate the impact of SDI, gender, age, and environmental risks on the disease burden.ResultsThe global CCVD incidence rose from 1,486,136.37 cases (95% UI: 1,115,077.02–1,959,529.28) in 1990 to 1,861,693.20 cases (95% UI: 1,335,751.17–2,531,859.51) in 2021, an increase of approximately 25.27%, with an EAPC of 0.43 (95% UI: 0.35–0.51). Incidence rates increased continuously in low and low-middle SDI regions, whereas they showed a marked decline in regions with high and high-middle SDI levels. CCVD mortality decreased markedly in high-SDI regions but remained persistently high in low SDI regions. Gender and age analyses revealed higher incidence and mortality rates among female children compared to males, with the 10–14 age group being the most affected. Low temperatures were identified as a primary driver of CCVD burden, particularly in low-SDI regions.ConclusionThe global CCVD burden exhibits significant inequalities, largely driven by disparities in public health resource levels across regions with varying SDI. These findings highlight persistent global health inequalities and underscore the need for region-specific interventions, especially in low-SDI regions where the CCVD burden is rising.